Angiotensin-converting enzyme 2 and kidney diseases in the era of coronavirus disease 2019 - Suh, Sang Heon (Korean J Intern Med, 2021)
In the decades since the discovery of angiotensin-converting enzyme 2 (ACE2), its protective role in terms of antagonizing activation of the classical renin-angiotensin system (RAS) axis has been recognized in clinical and experimental studies on kidney and cardiovascular diseases. The effects of ACE inhibitor/angiotensin type 1 receptor blockers (ACEi/ARBs) on ACE2-angiotensin-(1-7) (Ang-(1-7))-Mas receptor (MasR) axis activation has encouraged the use of such blockers in patients with kidney and cardiovascular diseases, until the emergence of coronavirus disease 2019 (COVID-19). The previously unchallenged functions of the ACE2-Ang-(1-7)-MasR axis and ACEi/ARBs are being re-evaluated in the era of COVID-19; the hypothesis is that ACEi/ARBs may increase the risk of severe acute respiratory syndrome coronavirus 2 infection by upregulating the human ACE2 receptor expression level. In this review, we examine ACE2 molecular structure, function (as an enzyme of the RAS), and distribution. We explore the roles played by ACE2 in kidney, cardiovascular, and pulmonary diseases, highlighting studies that defined the benefits imparted when ACEi/ARBs activated the local ACE2-Ang-(1-7)-MasR axis. Finally, the question of whether ACEi/ARBs therapies should be stopped in COVID-19-infected patients will be reviewed by reference to the available evidence.